Ruxolitinib in steroid refractory graft-vs.-host disease: a case report. Issue 1 (December 2016) - Maffini, Enrico; Giaccone, Luisa; Festuccia, Moreno; Brunello, Lucia; Buondonno, Ilaria; Ferrero, Dario; Boccadoro, Mario; Dellacasa, Chiara; Busca, Alessandro; Novero, Domenico; Bruno, Benedetto
Abstract Background Allogeneic hematopoietic stem cell transplantation (HSCT) is potentially curative in a variety of hematological malignancies. Graft-vs.-host disease (GvHD) remains a life-threatening complication. Standard treatment is high-dose (HD) corticosteroids. Steroid-refractory (SR) GvHD is associated with poor prognosis. At present, second-line treatment is ill-defined and includes a number of agents. Novel insights into the pathophysiology of acute GvHD (aGvHD) highlight the relevant role of the host inflammatory response governed by several kinase families, including Janus kinases (JAK)1/2. Ruxolitinib, a JAK1/2 inhibitor approved for intermediate-2/high-risk myelofibrosis, was recently employed in SR-GvHD with encouraging overall response rates. Clinical experience however remains limited. Case presentation A 51-year-old male with refractory anemia with excess blast type-2 underwent a myeloablative allogeneic HSCT from a 9/10 HLA-matched unrelated donor after conditioning with busulfan and cyclophosphamide. GvHD prophylaxis consisted of cyclosporine, methotrexate, and thymoglobulin. CD34+ cells/kg infused were 8.69 × 106  kg. On day 29, the patient developed overall grade IV aGvHD with biopsy proven stage IV gastrointestinal (GI) GvHD refractory to HD corticosteroids. Patient conditions rapidly deteriorated and became critical despite the addition of mycophenolate mofetil and budesonide. On day 33, Ruxolitinib was started, and on day 39 the patient clinical conditions gradually improved. Complete resolution of aGvHD was also confirmed by histology on day 54. Conclusions At 5 months from HSCT, the patient is well and in continuous hematological complete remission without flare of GvHD. Ruxolitinib was discontinued on day 156. Ruxolitinib is feasible and effective in SR-aGvHD though large prospective clinical trials are warranted.